The Implementation of Online Learning in Senior High School during the Corona Virus Pandemic - Rahayu, Istigh Fariana (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
The COVID-19 pandemic has catalyzed a significant shift from traditional face-to-face classes to online learning, profoundly impacting educational practices. This study employs a descriptive qualitative case study approach to investigate the implementation of online learning at MAN 2 Kota Kediri. Data were collected through questionnaires and structured interviews with English teachers to examine their challenges and experiences during this transition. Findings indicate that teachers effectively utilized the discovery learning model, which comprises three key stages: preliminary activities, core activities, and closing activities. Each stage includes critical steps such as stimulation, problem identification, data collection, data processing, and generalization. The results highlight the importance of structured online learning frameworks in enhancing educational outcomes during challenging times. Additionally, the study underscores the role of information technology in education and the necessity for planned, effective human resource development to boost productivity and community welfare. This research contributes valuable insights into the adaptation of teaching methodologies in the face of unprecedented challenges, emphasizing the effectiveness of active learning strategies in an online context.